2005
DOI: 10.1038/sj.onc.1208661
|View full text |Cite
|
Sign up to set email alerts
|

Expression of estrogen receptor α, retinoic acid receptor α and cellular retinoic acid binding protein II genes is coordinately regulated in human breast cancer cells

Abstract: Human breast cancer cell lines expressing the estrogen receptor a (ERa), all-trans-retinoic acid (ATRA) receptor a (RARa) and cellular retinoic acid binding protein II (CRABPII) genes are sensitive to ATRA-mediated growth inhibition. To study the relationship among ERa, RARa and CRABPII expression, the protein levels of each member were compared in five breast cancer cell lines (T47D, MCF-7, ZR-75-1, Hs587 T and MDA-MB-231 cells) and two immortalized nontumorigenic breast epithelial cell lines (MTSV1.7 and MCF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
44
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 43 publications
9
44
0
2
Order By: Relevance
“…Consistent with the present study, previous studies have reported that RARα was also involved in the regulation of the cell cycle in breast cancer (13). Retinoic acid, a ligand of RARα, inhibited the growth of breast cancer cells through the induction of cell cycle arrest at the G1 phase and cell apoptosis (13). The mechanism of RARα in the regulation of the development of LSCC is the focus of a number of studies; it has been reported that there are genomic and non-genomic influences (20).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Consistent with the present study, previous studies have reported that RARα was also involved in the regulation of the cell cycle in breast cancer (13). Retinoic acid, a ligand of RARα, inhibited the growth of breast cancer cells through the induction of cell cycle arrest at the G1 phase and cell apoptosis (13). The mechanism of RARα in the regulation of the development of LSCC is the focus of a number of studies; it has been reported that there are genomic and non-genomic influences (20).…”
Section: Discussionsupporting
confidence: 82%
“…It was indicated that the overexpression of RARα served an important function in the development of LSCC. Consistent with the present study, previous studies have reported that RARα was also involved in the regulation of the cell cycle in breast cancer (13). Retinoic acid, a ligand of RARα, inhibited the growth of breast cancer cells through the induction of cell cycle arrest at the G1 phase and cell apoptosis (13).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…30). The pCH110 plasmid that codes h-galactosidase was cotransfected into PC-3 and LNCaP cells using Lipofectmine 2000 (31). The cells were treated with or without AKBA (10 Ag/mL) for 24 h and then harvested for luciferase activity assay.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on MCF-cells support our data that RARα is the primer target of atRA (6). The decrease of RARα expression may affect RARβ2 transcription and further sensitivity of tumor cells to retinoids (7,34,35). Interestingly, BCA-2 cells constitutively expressed RARβ5, but not RARα, RARβ2, or RARγ proteins, suggesting significant post-translational defects in RAR signaling that correlated with cell resistance to retinoids both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%